Preliminary Study on Gas Storage Capacity and Gas-in-Place for CBM Potential in Balingian Coalfield, Sarawak, Malaysia - Kong Chai Chen, Kong (2011)
Abstract - The objective of this project is to predict the Coal Bed Methane (CBM) potential in Balingian coalfield, Sarawak. The geological survey shows that this area is about 120 km2. One out of six blocks in Balingian area is picked as an area of interest for preliminary assessment. Liang formation (Balingian Coal) is lignite coal with a mean vitrinite reflectance of 0.32%.The coal seam thickness is ranging from 0.33ft to 29.69ft. Based on the proximate analysis data from Geoscience and Mineral Department of Malaysia, the result show the moisture content is in between 12.9% to 18.7%. The volatile matter varies at 37.8% to 43.4%, whereas the fixed carbon ranges from 40.3% to 43.4%. The coal contains a very low ash content at mean of 2.7% and low sulphur content of less than 1%. Four core samples which were plugged from different coals have the range of porosity varies from 1.58% to 5.12%. Meanwhile, the permeability attained at minimum of 0.15mD to maximum of 46.15mD. Such a huge variation in porosity and permeability shows that they were due to the different number of cleat networks which were examined using PoroPerm. Gas storage capacity at different steps of pressure was determined from adsorption isotherm test which based on modified Boyle’s law. The result from the adsorption isotherm test showed the maximum adsorbed methane in the coal is 374.62scf/ton at maximum pressure of 1219.58psia. The linear regression of Langmuir Volume and Langmuir Volume showed 714.29scf/ton and 1024.5psia respectively. The value of maximum absorbed methane is used in gas-in-place calculation which yields 15.20Bscf in the area of 6.094km2. The result is then compared with other similar coal rank fields. As a conclusion, Balingian coal field showed a very good prospect to produce the first CBM in Malaysia based on this preliminary study.